2021
DOI: 10.1159/000515659
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Cross-Cultural Adaptation, and Psychometric Evaluation of the Swedish Version of ENDOCARE: An Instrument to Measure Patient Centeredness of Endometriosis Care

Abstract: <b><i>Objectives:</i></b> The need for quality improvement within endometriosis healthcare is widely acknowledged. The ENDOCARE questionnaire (ECQ) measures patient centeredness of endometriosis care. The aims of this study were (1) to translate and culturally adapt ECQ into Swedish, (2) to evaluate validity (construct validity), and (3) to measure reliability (internal consistency and test-retest reliability). <b><i>Design:</i></b> This is a cross-sectional rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…This number is higher than the original research conducted by the creators of the ENDOCARE questionnaire, 9 namely 34 ± 7 years and other studies conducted using a similar questionnaire in Amsterdam 10 as well as research in Sweden. 11 The age of the respondents in this study was also higher than the previous study in Palembang, Indonesia which showed that the majority of endometriosis patients seeking medical assistance had a mean age of 33.52 + 7.12 years. 12 These results showed that endometriosis patients in Indonesia seek help and get diagnosed much later than women in other countries.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This number is higher than the original research conducted by the creators of the ENDOCARE questionnaire, 9 namely 34 ± 7 years and other studies conducted using a similar questionnaire in Amsterdam 10 as well as research in Sweden. 11 The age of the respondents in this study was also higher than the previous study in Palembang, Indonesia which showed that the majority of endometriosis patients seeking medical assistance had a mean age of 33.52 + 7.12 years. 12 These results showed that endometriosis patients in Indonesia seek help and get diagnosed much later than women in other countries.…”
Section: Discussioncontrasting
confidence: 52%
“…Similar results were obtained in a study in Sweden, especially on the physical comfort dimension. 11 This result showed that patients in both countries where the questionnaire was adapted had a perception that the infrastructure and waiting time contributed to the worst experience in the treatment of endometriosis.…”
Section: Discussionmentioning
confidence: 94%
“…The ECQ has been validated to investigate the patient-centeredness of endometriosis care across Belgium, Sweden, and the Netherlands [18, 19, 21]. The ECQ includes 38 care aspects, grouped into ten dimensions of patient-centered care, to be rated on two 4-point Likert scales: one for importance and one for experienced performance [18, 19].…”
Section: Methodsmentioning
confidence: 99%
“…It can be used to compare patient-centeredness between different clinics and to identify targets for improvement [ 18 ]. ECQ is a valid, reliable, and disease-specific instrument that has been translated, cross-culturally adapted, and psychometrically evaluated in a Swedish context with good results [ 19 ].…”
Section: Methodsmentioning
confidence: 99%